(untitled) (Research, Society and Development, 2021)
A COVID-19 is a disease caused by infection with the SARS-CoV-2 virus. The pediatric population corresponds to 1 to 5% of confirmed cases of the disease, varying according to the country under study. This work aims to analyze suspected and confirmed cases of children and adolescents of COVID-19 in a hospital in Sergipe. This is a cross-sectional observational study involving 1,388 patients, under 20 years of age, during March 2020 and September 2021. Among patients, 54.8% were male, 10.4% had some comorbidities. It was observed that dyspnea was related to age, being frequent in children. In addition, some clinical manifestations were associated with SARS-CoV-2 infection, such as headache (p=0.021), diarrhea (p=0.002), respiratory distress (p<0.001), dyspnea (p<0.001), sneezing (p <0.001) and O2 saturation < 95% (p<0.001). There was a relationship between patients who progressed to death and some variables such as the presence of comorbidities, respiratory distress, sneezing, need for stabilization and ICU (p<0.001). Most pediatric cases are asymptomatic or mild, and children have a better outcome in COVID-19, as a small percentage evolves to death, usually associated with the presence of pre-hospital comorbidities.